Analisis Transparansi Pengelolaan Laporan Keuangan BUMDes Terhadap Laporan Aset Desa (Studi Kasus BUMDes Cinandang Kecamatan Dawarblandong Kabupaten Mojokerto) - Rohmah, Na’ila Sifaur; Askandar, Noor Shodiq; Sari, Arista Fauzi Kartika (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study was conducted to analyze the process of transparency in the management of BUMDes financial reports on asset reports from Cinandang Village, Dawarblandong District, Mojokerto Regency. The research method used in this study is a qualitative method with primary data sources and secondary data. Data collection techniques through documentation and interviews with village heads, BUMDES managers, and the community. The analytical method in this study uses descriptive and triangulation methods to achieve data validity from interviews and documentation. Based on the overall results of documentation and interviews with village heads, BUMDES managers and the community regarding transparency, village asset reports, BUMDES financial reports, and village financial accountability reports, the results obtained from this study illustrate those indicators for measuring the transparency of BUMDES financial report management towards the village asset report is appropriate. Therefore, it is concluded that the management of BUMDes financial reports on village asset reports is transparent in accordance with statutory regulations.Keywords: Transparency, BUMDES financial report, village asset report, village finance report